Refugee children in serbia during the Second World War - Nikolova, Maja (Moderna arhivistika, 2023)
Taking care of the refugees who came to Serbia during the Second World War required great efforts from both the state apparatus and the entire nation. Children who arrived in Serbia with parents who were unable to take care of them, as well as those without parental care, were a special problem. Serbian refugee homes were organized for these children, and some of them were cared for by Serbian urban and rural families. Young people of school age attended classes in Serbian schools, or in special classes formed at refugee homes. The state took care of their survival, food, clothing and health.
Keywords: begunska problematika; children's homes; druga svetovna vojna; familiy accommodation; nastanitev družin; otroški domovi; refugee issue; Second World War